Fostering efficacy and toxicity evaluation of traditional Chinese medicine and natural products: Chick embryo as a high throughput model bridging in vitro and in vivo studies. (July 2018) - Wu, Tong; Yu, Gui-Yuan; Xiao, Jia; Yan, Chang; Kurihara, Hiroshi; Li, Yi-Fang; So, Kwok-Fai; He, Rong-Rong
Graphical abstract: Abstract: Efficacy and safety assessments are essential thresholds for drug candidates from preclinical to clinical research. Conventional mammalian in vivo models cannot offer rapid pharmacological and toxicological screening, whereas cell-based or cell-free in vitro systems often lead to inaccurate results because of the lack of physiological environment. Within the avian species, gallus gallus is the first bird to have its genome sequencing. Meantime, chick embryo is an easily operating, relatively transparent and extensively accessible model, whose physiological and pathological alterations can be visualized by egg candler, staining and image technologies. These features facilitate chick embryo as a high-throughput screening platform bridging in vivo and in vitro gaps in the pharmaceutical research. Due to the complicated ingredients and multiple-targets natures of traditional Chinese medicine (TCM), testing the efficacy and safety of TCM by in vitro methods are laborious and inaccurate, while testing in mammalian models consume massive cost and time. As such, the productive living organism chick embryo serves as an ideal biological system for pharmacodynamics studies of TCM. Herein, we comprehensively update recent progresses on the specialty of chick embryo in evaluation of efficacy and toxicity of drugs, with special concerns of TCM.